Testing the Continuum/Spectrum Model in Russian-Speaking Children With and Without Developmental Language Disorder. - Gomozova, Militina; Lezzhova, Valeriia; Dragoy, Olga; Lopukhina, Anastasiya (Journal of Speech, Language & Hearing Research, 2024)
Purpose: Previously, Lancaster and Camarata (2019) showed that the continuum/ spectrum model of the developmental language disorder (DLD) best explained the high heterogeneity of symptoms in children with DLD. We hypothesize that the continuum/spectrum approach can include not only children with DLD but also typically developing (TD) children with different timelines and patterns of language acquisition. This model can explain individual language profiles and deficits in children. Method: We assessed language abilities in a group of Russian-speaking children with DLD aged 4–7 years (n = 53) and their age- and gender-matched peers without speech and language diagnoses (n = 53, TD). We evaluated the children’s performance at four language levels in production and comprehension domains, using 11 subtests of the standardized language assessment for Russian: Russian Child Language Assessment Battery (RuCLAB). Using the kmeans cluster method and RuCLAB scores, we obtained two clusters of children and analyzed their language performance in individual subtests. Results: The analysis revealed that the two clusters of children both included DLD and TD participants: Group 1, with higher test scores (TD = 45, DLD = 24 children), and Group 2, with lower scores (TD = 8, DLD = 29). Children from Group 1 mostly had lower scores at one of the language levels, whereas those from Group 2 struggled at several language levels. Furthermore, children with DLD from both groups tended to be more sensitive to linguistic features such as word length, noun case, and sentence reversibility compared to TD children. Conclusions: The presence of two mixed groups shows that children with diagnosed DLD could perform on par with TD children, whereas some younger TD children could perform similarly to children with DLD. Our findings support the continuum/spectrum model: Linguistic skills in preschool children are a continuum, varying from high to poor skills at all language levels in comprehension and production. To describe a child’s language profile, the tasks assessing all language levels should be used.